On some imbedding relations between certain sequence spaces - Mursaleen, M.; Noman, A. K. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
In the present paper, we introduce the sequence space l^λ_p of non-absolute type which is a p-normed space and a BK-space in the cases of 0 < p < 1 and 0 < p < 1 i 1 ≤ p < ∞, respectively. Further, we derive some imbedding relations and construct the basis for the space l^λ_p, where 1 ≤ p < ∞.